Spatial and Temporal Dynamics of Territorial Spatial Conflicts and Construction Land Expansion in Guizhou Province: A 40-Year Perspective - Huaiyu Wang; Liu Yang; Hongzan Jiao (Land)
Territorial spatial conflicts (TSCs) refer to a contradiction of utilization resulting from the inconsistency of the needs and objectives of different subjects of interest for spatial resources in planning, utilization, and management. This research aimed to unveil the TSCs, construction land expansion (CLE), and their relationship in Guizhou Province from 1980 to 2020, both temporally and spatially. This paper established indicators to assess CLE, including construction land expansion velocity, construction land expansion intensity, and construction land expansion pattern to analyze the expansion characteristics of construction land in Guizhou Province. At the same time, the territorial spatial conflict indicator (SCII) was constructed to study the TSCs in Guizhou Province, and its evolution pattern was explored through the cold hotspot analysis. On this basis, it investigated the relationship and linkage between TSCs and CLE through the ordinary least squares (OLS) regression model and geographically weighted (GWR) regression model. Furthermore, this paper also constructed an economic elasticity coefficient and a population elasticity coefficient to analyze the collaborative relationship between TSCs and GDP along with population volume. The research revealed that while the velocity and intensity of CLE in Guizhou Province have escalated over time, this expansion displayed considerable geographical variation across various locations. Simultaneously, the TSCs intensified, demonstrating a slight positive correlation with the expansion. The study of the spatial and temporal evolution characteristics and response relationship between the TSCs and CLE provided a reference for the optimization of regional territorial space. It is highly valuable and significant in fostering efficient utilization of land resources, adjusting to economic and social transformations, and improving the scientific rigor of spatial planning.